(1-m)(1 m) (m-2)^2-2(m 3)^2=1-m^2 m^2-4m 4-2m^2-12m-18=-2m^2-16m-13=-2(m^2 8mm-13又m^2 8m-1=0所以有m^2 8m=1所以-2(m^2 8m)-13=-2*1-13=-15
已知:m^2+8m-1=0.求(1-m)(1+m)+(m-2)^2-2(m+3)^2的值 ,有过程,谢谢!
2个回答
相关问题
-
已知m²+8m-1=0,求代数式(1-m)(1+m)+(m-2)²-2(m+3)²的值
-
已知m2+m+1=0,求(3m2-2m)-2(m2-[3/2]m)+1的值.
-
已知m^2+m+1=0,求m^2+1/m^2和(m-1/m)的值
-
已知m2+m-1=0,求m3+2m2-1997的值.【提示;m3+2m2-1997=(m3+m2-m)+(m2+m-1)
-
已知m2+m-1=0,求m3+2m2+3的值.
-
已知M2+M-1=0,求M3+2M2+2008的值
-
已知m^2-m+1=0,求m^2+m^-2的值
-
已知m+1/m=3,求m^2+1/m^2的值
-
已知m²+m+1=0,求(3m²-2m)-2(m²-2分之3吗)+1得值
-
若m-1/m=-1,求2m²+2m-3的值?若2m²-3m+1=0,求2m+1/m的值?